Biotechnological 2-Phenylethanol Production: Recent Developments - Ana R. S. Bernardino; Cristiana A. V. Torres; João G. Crespo; Maria A. M. Reis (Molecules)
2-Phenylethanol (2-PE) is a key flavor compound with a rose-like scent, used in the cosmetics, perfume, home care and food industries. This aroma compound can be obtained naturally from various flowers, however chemical synthesis is the most used route to meet market demand. The increasing interest in natural products has led to the development of more environmentally friendly alternatives for 2-PE production through biotechnological approaches. The most efficient approach involves the biotransformation of L-phenylalanine into 2-PE via the Ehrlich pathway, a process observed in different microorganisms such as yeasts and bacteria. 2-PE produced by this way can be considered as natural. However, due to the toxicity of the aroma to the producing microorganism, low production yields are typically obtained, motivating efforts to develop production processes that can overcome this bottleneck, enhance 2-PE yields and reduce the production costs. This review presents and discusses the latest advances in the bioproduction of 2-PE through microbial fermentation, in terms of producing strains, the optimization of cultivation processes, strategies to mitigate product toxicity, and the use of low value feedstocks. Novel applications for 2-PE are also highlighted.